2021
DOI: 10.1371/journal.pbio.3001121
|View full text |Cite
|
Sign up to set email alerts
|

CD74 is a regulator of hematopoietic stem cell maintenance

Abstract: Hematopoietic stem and progenitor cells (HSPCs) are a small population of undifferentiated cells that have the capacity for self-renewal and differentiate into all blood cell lineages. These cells are the most useful cells for clinical transplantations and for regenerative medicine. So far, it has not been possible to expand adult hematopoietic stem cells (HSCs) without losing their self-renewal properties. CD74 is a cell surface receptor for the cytokine macrophage migration inhibitory factor (MIF), and its m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Similarly, we found enrichment of stem-cell-related genes (MEG3 and HIF1a) complemented by lower expression of activation-related genes (CDK6 and CD74 (ref. 23 ); Extended Data Fig. 2l ).…”
Section: Resultsmentioning
confidence: 94%
“…Similarly, we found enrichment of stem-cell-related genes (MEG3 and HIF1a) complemented by lower expression of activation-related genes (CDK6 and CD74 (ref. 23 ); Extended Data Fig. 2l ).…”
Section: Resultsmentioning
confidence: 94%
“…As shown in Figure S2B, the LEFTY1+ cells also expressed CD44, another known stem cell marker (Ye et al, 2018). CCC analysis revealed that a signaling network of macrophage migration inhibitory factor (MIF), a ligand of the CD74+CD44 complex and CD74+CXCR4 complex (Becker-Herman et al, 2021; Shi et al, 2006), had characteristic features, i.e., many of MIF–(CD74+CD44) and MIF–(CD74+CXCR4) interactions are mediated by LEFTY1+ cells among all the cell types identified in gastric mucosa (Figure 7B). We conclude, therefore, that LEFTY1+ epithelial cells function as a hub of cellular communications via CD44 networks.…”
Section: Resultsmentioning
confidence: 99%
“…The multilayered interactions of LEFTY1+ cells with various other cells, including epithelial cell types, support our hypothesis that LEFTY1+ epithelial cells compose a possible stem cell cluster. CD74 is another communication partner of CD44, and the CD74–CD44 complex functions to prevent apoptosis and maintain stem cell properties (Becker-Herman et al, 2021; Gore et al, 2008; Shi et al, 2006). In contrast to other cell types, we found that a CD44 and CD74 coexpression pattern existed in LEFTY1+ epithelial cells (Figure S8B), providing further evidence that LEFTY1+ possible stem cells function in concert with the CD44 network.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of the interaction in AML was due to significant downregulation of CD74 expression, which occurred in 13 out of the 19 BM cell types. Loss of CD74 expression may contribute to enhanced fitness of leukemic HSC.MPPs, as CD74 has been reported to regulate HSPC maintenance and its deficiency in mice caused accumulation of HSPCs in the BM due to their increased potential to compete for BM niches [36].…”
Section: Resultsmentioning
confidence: 99%